Cultura Corporal Popular como contenido del curriculo multicultural de Educación Física Popular Body Culture as part of a multicultural syllabus in Physical Education A Cultura Corporal Popular como conteúdo do currículo multicultural da Educação Física (Universidade Federal de Goiás, 2008)
Schools have harbored a manifold of cultural identities since education became accessible to all. Historically, however, knowledge from minority groups was never accepted into the school syllabus and dominant culture prevailed, thus calling for urgent studies to be made in order to show ways of transforming the current state of affairs. This action research project aims at developing a multicultural syllabus for physical education that stems from the heritage of popular body culture. Results gathered through critical analysis of experience show that popular culture contents and ethnography-based teaching methodologies can promote the strengthening of a community's cultural identity. Keywords: Multiculturalism - popular culture - syllabus. Con la democratización del acceso, la escuela recibió múltiples identidades culturales. Históricamente, los conocimientos de los grupos desprovistos de poder fueron negligenciados en el currículo dominante, así despunta como urgente la realización de estudios que indiquen caminos para una transformación de ese cuadro. Esta investigación-acción buscó desarrollar un currículo multicultural para Educación Física a partir del patrimonio de la cultura corporal popular. Los resultados, a través del análisis crítico de la experiencia, indican que los contenidos de la cultura popular y la metodología de enseñanza inspirada en la etnografía proporcionaron el fortalecimiento de la identidad cultural de la comunidad. Palabras-clave: Multiculturalismo - cultura popular - currículo. Com a democratização do acesso, a escola acolheu múltiplas identidades culturais. Historicamente, os conhecimentos dos grupos desprovidos de poder foram negligenciados no currículo e a cultura dominante prevaleceu, despontando como urgente a realização de estudos que indiquem caminhos para a transformação desse quadro. Esta pesquisa-ação busca desenvolver um currículo multicultural para a Educação Física a partir do patrimônio da cultura corporal popular. Os resultados, obtidos por meio da análise crítica da experiência, indicam que os conteúdos da cultura popular e a metodologia de ensino inspirada na etnografia proporcionaram o fortalecimento da identidade cultural da comunidade. Palabras-chave: Multiculturalismo - cultura popular - currículo.